2004
DOI: 10.1021/jp0479421
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced, Controlled Generation of Palladium Crystallite Structures in Polyimide Films

Abstract: Structures of Pd crystallites with nanometer dimensions are formed on the surface of and inside polyimide films by a combination of photochemical and thermal processes. Photoinduced transformations of polyamic acid films containing Pd 2+ complexes prior to thermal curing affect the subsequent thermal imidization of the polymer and reduction of the remaining palladium ions. The extent of photolysis controls the formation and characteristics of surface and subsurface metallic layers as well as the sizes of Pd pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In contrast with the chemical synthesis, the usage of photochemical synthesis is a promising method that offers spatial and temporal control, and the regulation of reduction rate can be achieved simply by adjusting the incident UV light intensity. In recent publications these issues have been related to the photochemical synthesis of metal nanoparticles. For example, Mills et al reported the photochemical generation of colloidal Ag, Pd, and Pt nanoparticles in octane containing oleoyl sarcosine as a particle stabilizer and benzophenone as a sensitizer. Scaiano et al also demonstrated an elegant and straightforward way to obtain aqueous dispersions of unprotected Au nanoparticles using a hydrophilic benzoin derivatives, Irgacure-2959, that under UV irradiation gives strongly reducing ketyl radicals.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with the chemical synthesis, the usage of photochemical synthesis is a promising method that offers spatial and temporal control, and the regulation of reduction rate can be achieved simply by adjusting the incident UV light intensity. In recent publications these issues have been related to the photochemical synthesis of metal nanoparticles. For example, Mills et al reported the photochemical generation of colloidal Ag, Pd, and Pt nanoparticles in octane containing oleoyl sarcosine as a particle stabilizer and benzophenone as a sensitizer. Scaiano et al also demonstrated an elegant and straightforward way to obtain aqueous dispersions of unprotected Au nanoparticles using a hydrophilic benzoin derivatives, Irgacure-2959, that under UV irradiation gives strongly reducing ketyl radicals.…”
Section: Introductionmentioning
confidence: 99%
“…These peaks are attributed to the (111), (200) and (220) of face -centered cubic palladium. The broad peak centered at 19° 2 theta is due to the main chain of the polymer [10]. Interestingly, at 10 minutes treatment using NaOH, a complete disappearance of the peak from the polymer structure was observed, whereas at all other treatment times the peak remained.…”
Section: B Xrd On Pd Modified Pi Filmsmentioning
confidence: 95%
“…Similar trends have been observed for cellulose fibers containing Pt nanoparticles and polyimide films containing Fe nanoparticles, both of which resulted in the formation of a carbon matrix through carbonization (pyrolysis) of the matrix at high temperatures. Oxidative degradation of thick polyimide films containing Ag nanoparticles was also observed, but resulted in a broad size distribution and inhomogeneous distribution of the nanoparticles in the film 7b. In the current process, however, a different mechanism for metal-catalyzed decomposition is operative.…”
mentioning
confidence: 94%
“…Herein, we report a novel method to control the average interparticle spacing among metal nanoparticles embedded in a polyimide matrix based on an in situ approach using ion-doped precursors. , This is achieved by the metal-catalyzed decomposition of the surrounding matrix, which induces a decrease in thickness (i.e., volume) of the composite layer, while the nanoparticle size remains intact (Figure A). This holds great promise not only toward the fundamental understanding of the physical interactions among metal nanoparticles but also toward the development of novel nanocomposites with tailored microstructures.…”
mentioning
confidence: 99%